The Crisis After the Crisis: Neoliberalized Discourses of Urgency, Risk and Resilience in the Reconstruction of Lac-Mégantic - Gilbert, Liette (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 2018)
This article examines how discourses of urgency, risk and resilience were mobilized in the reconstruction phase of Lac-Mégantic in the aftermath of the violent train derailment of July 2013. These discursive practices are central to rendering the existing built environment obsolete and allowing for redevelopment and reconstruction through expropriation and demolition. The manipulative discourses deployed in Lac-Mégantic utilize urgency to justify legislation than enables appropriation and demolition while creating the appearance of asking people to participate to reinvent their city. The mobilization of a risk and public insecurity logic about decontamination served as an alibi for demolishing the remaining downtown to clear the way for new real estate investments. It was also about emotionalizing resilience as a way to discredit contestation and instill acceptance and support for reconstruction efforts. The reconstruction process is deemed a crisis after the July 2013 crisis.